Fazenda Velha: os efeitos da modernização numa povoação rural no município de Formiga-MG - Marcio Zacarias Lara (1990)
The forget of this study is to analise, together with the community-leaders of the village Fazenda Velho (old farm), Formiga, MG-Brazil, the affects of the process of modernization occurred in the place in consenquence of the MG II program. Considering modernization according to the latin root"modernus","present" we touch two different ranges.The first os Marschall Berman, qualifying modernization as responsable for "the destruction of everyting we have and we are".The second, preconized by Marcello Azevedo, as a cultural reality, independing upon capitalist or socialist systems, and therefore existing in the liberal tradition as well as in the Marxist or comunist ones.We come to the conclusion that through the project and actions of the program, developped between the small producers, the realized modernization had the meaning of "humanization of the existence of the people"rather than being and element to disturb the balance or the equilibrium of the structures, underling local life. However the renewal happened without transformig structurally Fazenda Velhha, surely in had a role in the reproduction of a more critival and more participating farmer who, notwithstanding his internalising of the reasonability of the capital, will know to face the struggle amidst the contradictions of this same capital